Nickel-Doped Ceria Bifunctional Electrocatalysts for Oxygen Reduction and Evolution in Alkaline Media - Milikić, Jadranka (2022)
Nickel-doped ceria (Ce1−xNixO2−δ) nanopowders (7 to 5 nm in size) synthesized by the cation complexation method with 5, 10, 15, and 20 Ni at.% are studied with respect to their electrochemical activity for the oxygen reduction (ORR) and oxygen evolution (OER) reactions in alkaline medium. One finds good bifunctional electrocatalytic activity of the four Ce1−xNixO2−δ electrocatalysts. The Tafel analysis of the ORR in the 0.57–0.78 V vs. RHE potential window leads to slopes in the 70–108 mV dec−1 range. The number of electrons exchanged during ORR is between 2 and 2.7. The OER Tafel slopes are determined to be in the range 192 –281 mV dec−1. OER activation energies are found to range between 28 and 43 kJ mol−1. The specific capacitance of Ce1−xNixO2−δ electrocatalysts measured at a scan rate of 100 mV s−1 varies between 0.7 and 1.4 Fg−1. The results demonstrate that Ce1−xNixO2−δ nanopowders can act as bifunctional electrocatalysts for ORR/OER for potential application in the oxygen electrode of devices such as rechargeable metal–air batteries.